Usual diet quality among 8- to 12-year-old Brazilian children - Paula Martins Horta; Eliseu Verly Junior; Luana Caroline dos Santos (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2019)
Abstract: Nutritional surveys are important information sources for public policy in the food and nutrition field. They focus on assessing usual dietary patterns, because health outcomes result from the long-term intake. Here we aimed to evaluate diet quality adjusted for day-to-day variance among Brazilian children. Data were collected between March 2013 and August 2015. The sample included 8- to 12-year-old children (n = 1,357) from public schools from all administrative regions of a Brazilian city. One 24-h dietary recall (24HR) was collected for the whole sample and two 24HR for two non-consecutive days of the same week for a subsample. The Healthy Eating Index-2010 (HEI-2010) was adapted to Brazilian food habits and the Brazilian dietary guidelines were used to evaluate diet quality. Statistical analysis included a multipart, nonlinear mixed model with correlated random effects proposed by the U.S. National Cancer Institute to correct diet quality for day-to-day variance. The adapted HEI-2010 total score was 51.8. Children with poorer diet quality (< 10th percentile) scored less than 41.1, and children with higher diet quality (> 90th percentile) scored more than 62.4. The overall adequacy of adapted HEI-2010 components was low. Higher adequacy percentages were identified for total protein foods (94.9%), greens (62.3%), and seafood and plant proteins (52.2%). Seven components showed less than 10% of adequacy: refined grains, fatty acids, dairy, sodium, total vegetable, whole grains, and empty calories. This study identified the main inadequacies among children's diet quality, which can guide promotion actions for healthy eating.